Public knowledge, attitudes, social distance and reported contact regarding people with mental illness 2009–2015. (August 2016) - Henderson, C.; Robinson, E.; Evans‐Lacko, S.; Corker, E.; Rebollo‐Mesa, I.; Rose, D.; Thornicroft, G.
Abstract : Objective: To investigate whether public knowledge, attitudes, desire for social distance and reported contact in relation to people with mental health problems have improved in England during the Time to Change (TTC) programme to reduce stigma and discrimination 2009–2015. Methods: Using data from an annual face‐to‐face survey of a nationally representative sample of adults, we analysed longitudinal trends in the outcomes with regression modelling using standardised scores of the measures overall and by age and gender subgroups. Results: There were improvements in all outcomes. The improvement for knowledge was 0.17 standard deviation units in 2015 compared to 2009 (95% CI 0.10, 0.23); for attitudes 0.20 standard deviation units (95% CI 0.14, 0.27) and for social distance 0.17 standard deviation units (95% CI 0.11, 0.24). Survey year for 2015 vs. 2009 was associated with a higher likelihood of reported contact (OR 1.32, 95% CI 1.13, 1.53). Statistically significant interactions between year and age suggest the campaign had more impact on the attitudes of the target age group (25–45) than those aged over 65 or under 25. Women's reported contact with people with mental health problems increased more than did men's. Conclusion: The results provide support for the effectiveness of TTC.